Fusion imaging to support endovascular aneurysm repair using 3D-3D registration - Schulz, Christof; Böckler, Dittmar; Geisbüsch, Philipp (Journal of endovascular therapy, 2016)
Purpose: To evaluate the feasibility and accuracy of fusion imaging (FI) during endovascular aneurysm repair (EVAR). Methods: FI was performed in 101 consecutive EVAR patients (median age 72 years; 93 men) using automatic registration of the preoperative computed tomography angiography (CTA) with an intraoperative noncontrast cone beam CT (nCBCT; 3D-3D registration). Operative landmarks defined on the CTA were then overlaid in 3 dimensions on fluoroscopy images. Accuracy was measured as the deviation of the position of the lowest renal artery between the FI and angiography. Factors potentially influencing accuracy (α angle, β angle, anesthesia, tortuosity index, neck calcification, neck length, CTA slice thickness, and conventional or sac sealing stent-graft) were analyzed in a multivariate linear regression model. Results: Median procedure time for nCBCT was 3 minutes (range 2-20), with 4 minutes (range 0.4-15) for registration. An automatic registration tool was used successfully in 90 (89%) patients. Median craniocaudal deviation of the FI was 3 mm (range 0-15). Full accuracy (<1-mm deviation) was seen in 23 (23%) patients, 1- to 3-mm deviation in 23 (23%), 4- to 5-mm deviation in 22 (22%), and >5-mm deviation in 33 (33%). Caudal deviation potentially resulting in renal coverage was seen in 9 (9%). Lateral plus craniocaudal deviation was a median 5.8 mm (range 0-22). The position of the lowest renal artery compared to the FI was left and cranial in 62 (61%). Aneurysm morphology (β angle, p=0.04), CTA slice thickness (p=0.02), and the use of 2 stiff guidewires in endovascular aneurysm sealing (p=0.01) influenced the overlay accuracy. Conclusion: Fusion imaging can be integrated into a daily workflow adding little to the procedure time. Craniocaudal accuracy (<5 mm) was achieved in 68% of cases, allowing optimal C-arm and angiographic catheter positioning or cannulation of target vessels in most patients. However, the accuracy of FI does not allow a noncontrast EVAR procedure without confirmation of FI overlay by a minimal contrast injection or vessel cannulation.